Laser processing device, method for preparing metal electrode and photovoltaic cell

Through the combination of laser processing system and CuO/Cu2O nanoparticle copper electrode slurry, the problem of complex and high cost of copper electrode process in silicon heterojunction solar cells is solved, and high efficiency and low cost copper electrode preparation is achieved, which improves solar cells conversion efficiency.

CN119451295APending Publication Date: 2025-02-14GUANGDONG UNIV OF TECH +1

Patent Information

Application Number
CN202310945085.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art When preparing silicon heterojunction solar cell copper electrodes, the process is complex and costly, and the bonding force between the copper electrode and the substrate is insufficient, which limits the reduction of the conversion efficiency and manufacturing cost of the solar cell.

Method used

Using a laser processing system, through the composite method of pulsed laser and continuous laser, selective metallization is achieved while remelting and solidification is carried out, increasing adhesion and reducing the internal stress of the electrode. Meanwhile, CuO and/or Cu2O nanoparticles are used as the precursor material for the copper electrode slurry to enhance the bonding force of the copper circuit.

Benefits of technology

The process flow is simplified, the processing efficiency is improved, the problems of electrode aspect ratio and bonding force are solved, the manufacturing cost of solar cells is reduced, and the photoconversion efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451295A_ABST
    Figure CN119451295A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photovoltaic cells, and provides a laser processing device, a method for preparing a metal electrode and a photovoltaic cell. According to the laser processing system, remelting and solidification are carried out while selective metallization is carried out, the internal stress of the electrode is released while the adhesive force is increased, and the porosity can be effectively reduced; in addition, the technological process can be simplified, the problem that the secondary machining position is difficult to calibrate is solved, and the machining efficiency is improved. According to the method for preparing the metal electrode, the position of the copper electrode can be precisely machined, the problem of precision of current silk-screen printing is solved, damage to the amorphous silicon layer can be avoided, the prepared copper electrode has the large height-width ratio, and the light conversion efficiency can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaic cells, and in particular to a laser processing device, a method for preparing a metal electrode and a photovoltaic cell. Background Art

[0002] Silicon heterojunction (HJT) cells are a type of high-efficiency solar cell. They have become one of the most promising solar cell technologies due to their advantages such as simple process, high conversion efficiency, low-temperature process, and double-sided power generation. The metal grid electrode is the most important structure and material in silicon heterojunction cells. Its main function is to collect carriers generated by the photovoltaic effect, thereby drawing out the current generated by the photovoltaic effect.

[0003] At present, the most commonly used method for preparing electrodes in the industry is screen printing silver paste, which has the advantages of simple and mature process and suitable for mass production. However, due to the precision of the printing plate, the electrode aspect ratio is small, the shading area is large, the screen printing process is becoming more and more difficult, and the yield rate caused by virtual printing and broken grids has dropped significantly, which limits the further improvement of the conversion efficiency of solar cells. On the other hand, due to the inherent characteristics of HJT cells, the processing technology needs to be controlled at around 200°C, and low-temperature silver paste needs to be used. However, low-temperature silver paste has poor conductivity, high contact resistance with ITO film (Transparent Conductive Oxide), poor printing performance, and a large weight gain of the paste of the heterojunction battery, accounting for about 30-40% of the cost of the entire heterojunction processing battery. In addition, the price of silver paste is expensive, which makes the manufacturing cost of solar cells high, which is not conducive to the development of batteries in the direction of high efficiency and low cost.

[0004] In order to reduce costs and increase efficiency, more and more solar cell manufacturers have turned to the development of copper electrodes with high conductivity and low cost. The most commonly used method at present is electroplating. The electroplating preparation of copper grid electrode is to first deposit a layer of seed copper on the surface of ITO, then pattern the mask, and then electroplate copper and tin. However, this method needs to consider the subsequent etching and removal of the mask and seed layer. The process is relatively cumbersome, and the bonding strength between the copper electrode and the substrate has always been a problem in the industry.

[0005] Therefore, it is of great significance to develop a method for preparing copper electrodes for silicon heterojunction solar cells with simple process and low cost. Summary of the invention

[0006] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art, and to provide a laser processing device, a method for preparing a metal electrode using the laser processing device, and a photovoltaic cell containing a metal electrode obtained by the preparation method. The laser processing system realizes remelting and solidification during selective metallization, increases adhesion while releasing the internal stress of the electrode, and can effectively reduce the porosity; it can also simplify the process flow, solve the problem of difficult position calibration of secondary processing, and improve processing efficiency. The method for preparing a metal electrode can accurately process the position of the copper electrode, solve the current problem of screen printing accuracy, and avoid damage to the amorphous silicon layer. The prepared copper electrode has a large aspect ratio, which can effectively improve the light conversion efficiency.

[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a laser processing system for preparing a metal electrode of a solar cell, the laser processing system comprising: a mobile working platform, a first optical path system, a second optical path system and a composite optical path system;

[0008] The mobile working platform is used to carry the substrate of the metal electrode to be prepared;

[0009] The first optical path system includes a pulse laser and a first optical path adjustment system, the pulse laser is used to emit a pulse laser, and the pulse laser passes through the first optical path adjustment system to form a first light beam;

[0010] The second optical path system comprises a continuous laser and a second optical path adjustment system, wherein the continuous laser is used to emit a continuous laser, and the continuous laser passes through the second optical path adjustment system to form a second light beam;

[0011] The composite optical path system receives the first light beam and the second light beam to form a composite light beam, and the composite light beam acts on the substrate of the metal electrode to be prepared.

[0012] A second aspect of the present invention provides a method for preparing a metal electrode, which uses the laser processing system and copper electrode slurry described in the first aspect of the present invention to prepare the metal electrode.

[0013] A third aspect of the present invention provides a photovoltaic cell, comprising a metal electrode, wherein the metal electrode is prepared by the method described in the second aspect of the present invention.

[0014] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0015] (1) The laser processing system provided by the present invention adopts a pulsed laser and a continuous laser composite method to achieve remelting and solidification during selective metallization, thereby increasing adhesion and releasing the internal stress of the electrode, which can effectively reduce the porosity; it can also simplify the process flow, solve the problem of difficult secondary processing position calibration, and improve processing efficiency.

[0016] (2) The method for preparing a metal electrode provided by the present invention uses a copper electrode slurry using CuO and / or Cu2O nanoparticles as a precursor material, which has the advantages of good dispersibility and good reducibility, can effectively increase the bonding strength inside the copper circuit and with the substrate, and replaces the use of expensive silver paste, greatly reducing the production cost of solar cell electrodes, and can well meet the needs of high efficiency and low cost in industrial production.

[0017] (2) The method for preparing metal electrodes provided by the present invention can accurately process the position of the copper electrode due to the high controllability of laser processing, thus solving the current problem of screen printing accuracy. The prepared copper electrode has a larger aspect ratio.

[0018] (3) The method for preparing a metal electrode provided by the present invention adopts a multiple scanning method, which effectively solves the problem of poor adhesion between the copper electrode and the substrate by realizing the remelting and solidification of the copper electrode. At the same time, it avoids the step of high-temperature curing in a sintering furnace, reduces damage to the amorphous silicon layer, and improves the light conversion efficiency.

[0019] (4) Compared with the traditional seed layer plating method, the solar cell preparation method provided by the present invention does not require a mask, avoids the processes such as mask patterning and seed layer removal, simplifies the process and reduces the cost; and the processed pattern can be directly and flexibly changed through drawing software such as CAD, so that complex copper electrode circuit morphology can be processed more flexibly.

[0020] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Shown is a schematic structural diagram of a laser processing system in an example of the present invention.

[0022] Figure 2 The figure shows a process flow chart for preparing copper electrodes for solar cells in one embodiment of the present invention.

[0023] Figure 3 The figure shows a schematic diagram of the process for preparing a copper electrode for a heterojunction battery in one example of the present invention.

[0024] Figure 4 FIG. 1 is a schematic diagram of a laser processing operation in an embodiment of the present invention.

[0025] Figure 5 Shown is a three-dimensional morphology of a copper electrode of a heterojunction battery in an example of the present invention.

[0026] Figure 6 Shown is an electron microscope image of the metal electrode copper circuit obtained in Example 1 of the present invention.

[0027] Figure numerals: 1-pulse laser; 2-wave plate; 3-first beam expander; 4-first reflector; 5-second reflector; 6-polarization reflector; 7-continuous laser; 8-second beam expander; 9-third reflector; 10-diffraction optical element; 11-galvanometer; 12-positioning sensor; 13-field mirror; 14-monitoring equipment; 15-sample to be processed; 16-mobile working platform; 17-heterojunction battery substrate; 18-metal electrode; 19-copper electrode slurry coating; 20-laser composite beam. DETAILED DESCRIPTION

[0028] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0029] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0030] A first aspect of the present invention provides a laser processing system for preparing a metal electrode of a solar cell, the laser processing system comprising: a mobile working platform, a first optical path system, a second optical path system and a composite optical path system;

[0031] The mobile working platform is used to carry the substrate of the metal electrode to be prepared;

[0032] The first optical path system includes a pulse laser and a first optical path adjustment system, the pulse laser is used to emit a pulse laser, and the pulse laser passes through the first optical path adjustment system to form a first light beam;

[0033] The second optical path system includes a continuous laser and a second optical path adjustment system, the continuous laser is used to emit continuous laser light, and the pulsed laser passes through the second optical path adjustment system to form a second light beam;

[0034] The composite optical path system receives the first light beam and the second light beam to form a composite light beam, and the composite light beam acts on the substrate of the metal electrode to be prepared.

[0035] In one example, the mobile working platform can be a two-dimensional mobile working platform or a three-dimensional mobile working platform. When the laser processing system is used to prepare metal electrodes of solar cells, the working platform is stationary and the galvanometer performs patterning according to a preset processing pattern.

[0036] In one example, the mobile working platform is a three-dimensional mobile working platform, which can move in the z-axis direction, and further can adjust the distance between the field lens and the processed object so that the focus of the composite light beam is focused on the surface of the processed object.

[0037] In one example, the pulse laser emitted by the pulse laser is not limited in terms of laser pulse width and wavelength, and the pulse width may be femtosecond laser, picosecond laser or continuous laser.

[0038] In one example, if Figure 1 As shown, the first optical path adjustment system includes a first optical element 2, a first beam expander 3 and a first reflector group which are arranged in sequence, wherein the first optical element 2 is close to the pulse laser 1, the first reflector group is close to the composite optical path system, and the first optical element is used to adjust the polarization of the pulse laser.

[0039] In the present invention, in the first optical path adjustment system, the first beam expander can expand and collimate the laser beam output by the pulsed laser, reduce the spot size, and improve the accuracy of laser processing; the first reflector group can change the direction of the expanded and collimated laser beam.

[0040] In one example, if Figure 1 As shown, the first optical element may be a half-wave plate 2, which can change the polarization of polarized light, for example, can change the polarization of the light beam by an angle of 180°.

[0041] In one example, the diffractive optical element may be a spatial light shaper, which may shape a Gaussian beam into beams of different shapes to flexibly meet various processing requirements. The shapes may be, for example, circular, elliptical, rectangular, square, linear, triangular, etc.

[0042] In one example, if Figure 1 As shown, the second optical path adjustment system includes a second beam expander 8 and a third reflector 9 which are arranged in sequence, wherein the second beam expander 8 is close to the continuous laser 7, the third reflector 9 is close to the composite optical path system, and the third reflector 9 is arranged at a first preset angle with the second beam expander 8.

[0043] In one example, the first preset angle can be freely adjusted according to the required light path direction, for example, it can be freely set within the range of 0-180 degrees (excluding the endpoint value).

[0044] In one example, the first preset angle may be 45 degrees or 135 degrees.

[0045] In one example, if Figure 1 As shown, the first reflector group includes a first reflector 4 and a second reflector 5, the first reflector 4 is close to the first beam expander 3 and is arranged at a second preset angle with the first beam expander 3, the second reflector 5 is arranged parallel to the first reflector 4, and the second reflector 5 is close to the composite optical path system.

[0046] In one example, the second preset angle can be freely adjusted according to the required light path direction, for example, it can be freely set within the range of 0-180 degrees (excluding the endpoint value).

[0047] In one example, the second preset angle may be 45 degrees or 135 degrees.

[0048] In one example, if Figure 1 As shown, the composite optical path system includes a polarizing reflector 6, a diffractive optical element 10, a galvanometer 11 and a field lens 13 arranged in sequence. The polarizing reflector 6 is close to the second reflector 5 and the third reflector 9, and the field lens 13 is close to the mobile working platform 16.

[0049] In one example, the polarizing reflector and the second reflector are arranged at a third preset angle to completely transmit the first light beam. The polarizing reflector has the same transmission direction as the pulsed laser to completely transmit the pulsed laser through the polarizing reflector.

[0050] In one example, the third preset angle can be freely adjusted according to the required light path direction, for example, it can be freely set within the range of 0-180 degrees (excluding the endpoint value). The third preset angle can be understood as the angle formed by the polarizing reflector and the second reflector.

[0051] In one example, the third preset angle may be 45 degrees or 135 degrees.

[0052] In one example, the polarizing reflector is arranged in parallel with the third reflector to partially transmit the second light beam. The polarizing reflector is arranged in parallel with the third reflector to partially transmit the continuous laser beam through the polarizing reflector.

[0053] Exemplarily, the polarizing reflector may be a 45° polarizing beam splitter, which can transmit light of a selected polarization direction and reflect other light perpendicular to the polarization direction, and the half-wave plate is used to make the pulsed laser beam and the 45° polarizing reflector transmit in the same direction, so that the pulsed laser beam is completely transmitted through the polarizing reflector. The continuous laser emits a laser beam in a randomly polarized state, and only a portion of the beam can pass through the polarizing reflector, thereby realizing the combination of the pulsed laser beam and the continuous laser beam to form a composite beam.

[0054] The galvanometer controls the composite light beam to perform laser selective metal patterning to prepare metal electrodes according to a set processing path; the field mirror can be an f-θ flat field scanning lens, which can focus the laser beam onto the surface of the sample to be processed.

[0055] In one example, if Figure 1 As shown, the laser processing system further includes a monitoring device 14, which is coaxially arranged with the galvanometer 11 and is used to monitor the processing process of the composite light beam.

[0056] In one example, the monitoring device can monitor the processing process of the composite light beam in real time.

[0057] The monitoring device is a monitoring device with an autofocus system. Exemplarily, the monitoring device may be a charge coupled device (CCD) camera, which may also be called a CCD image sensor, and which can convert an optical image into a digital signal.

[0058] It should be noted that the "coaxial setting" does not refer to a physical connection, but only an optical connection. The coaxial setting can be understood as keeping the optical axis of the CCD camera and the rotation axis of the galvanometer as close to the same straight line as possible to ensure that the light can accurately pass through the galvanometer into the imaging area of ​​the CCD camera. By coaxially calibrating the CCD camera, the CCD camera and the galvanometer can be coaxially visually positioned to achieve real-time observation of the relative position of the laser beam and the workpiece to be processed, as well as real-time monitoring of the processing process.

[0059] In one example, if Figure 1 As shown, the laser processing system further includes a positioning sensor 12, which is disposed on the galvanometer 11 and is used to determine the processing position of the composite light beam. The positioning sensor 12 can be disposed below the galvanometer 11 and close to the field lens 13 to facilitate accurate processing of the metal electrode position.

[0060] In one example, referring to Figure 1The schematic diagram of the laser processing system includes a first optical path system, a second optical path system and a composite optical path system, wherein the first optical path system includes a pulse laser 1, a first optical element 2 (half-wave plate), a first beam expander 3, a first reflector 4, and a second reflector 5 arranged in sequence; the second optical path system includes a continuous laser 7, a second beam expander 8, and a third reflector 9 arranged in sequence; the composite optical path system includes a polarization reflector 6, a diffractive optical element 10 (spatial light shaper), a galvanometer 11, a positioning sensor 12, a field lens 13, and a CCD camera 14 arranged in sequence; the composite optical path system receives the first light beam and the second light beam and forms a composite light beam, and the composite light beam is focused on the surface of the processing sample 15 located on the motion platform 16.

[0061] In one example, the process of preparing a metal electrode of a solar cell using the laser processing system may include the following steps:

[0062] Step 1: Start the mobile working platform and place the sample to be processed under the laser scanning system;

[0063] Step 2: Start the pulse laser and the continuous laser to emit a laser beam. The laser beam emitted by the pulse laser passes through the half-wave plate, the first beam expander, the first reflector, and the second reflector in sequence to form a first beam. The output optical path of the continuous laser passes through the second beam expander and the third reflector in sequence to form a second beam. The first beam and the second beam pass through the polarizing reflector, the diffractive optical element, the galvanometer (also called the scanning galvanometer) and the field mirror in sequence to form a coaxial composite beam.

[0064] Step 3: By positioning the sensor system and the CCD camera system, the coaxial composite light beam after the composite is focused at the relative position of the surface of the sample to be processed.

[0065] Step 4: Use a scanning galvanometer to control the composite laser beam to perform metal patterning on the surface of the sample to be processed according to a preset scanning area.

[0066] A second aspect of the present invention provides a method for preparing a metal electrode, which uses the laser processing system and copper electrode slurry described in the first aspect of the present invention to prepare the metal electrode.

[0067] In one example, the copper electrode slurry includes a metal composition, a dispersing reducing agent and a composite curing agent; the metal composition includes at least copper powder, and optionally gold powder and / or silver powder; the composite curing agent includes a thermosetting resin and a latent curing agent.

[0068] It should be noted that, in addition to copper powder, the metal composition may also contain gold powder and / or silver powder, as well as other metal powders with good electrical conductivity. The metal composition may be a combination of one or more of various forms of the above-mentioned metal elements, such as simple substances, oxides, hydroxides or salts, which is not limited and can be selected according to actual needs. For example, the metal composition may be a combination of three metal simple substances of copper, gold and silver, or may be a combination of three metal oxides.

[0069] In one example, the metal composition is in powder form, and the particle size is nanometer scale.

[0070] In one example, the metal composition includes nano copper oxide and / or nano cuprous oxide.

[0071] In one example, the metal composition is nano copper oxide.

[0072] In one example, the metal composition is nano cuprous oxide.

[0073] In one example, the metal composition is a composition of nano-copper oxide and nano-cuprous oxide. The ratio of the two is not limited and can be adjusted according to the actual sequence. Exemplarily, the mass ratio of nano-copper oxide to nano-cuprous oxide can be (1-5):1.

[0074] The copper electrode slurry of the present invention has the advantages of good dispersibility and high reduction rate, and the composite curing agent prepared by using a thermosetting resin and a latent curing agent can make the bonding force of the electrode prepared by the copper electrode slurry higher.

[0075] In one example, the mass ratio of the metal composition to the composite curing agent is (7-30):1, for example, it can be 7:1, 10:1, 12:1, 15:1, 16.4:1, 18:1, 20:1, 22:1, 25:1, 28:1, 30:1.

[0076] In a preferred embodiment, the mass ratio of the metal composition to the composite curing agent is (15-20):1.

[0077] In order to further improve the performance of the copper electrode slurry and prepare a metal electrode with better physical properties, one or more of the characteristics may be optimized.

[0078] In one example, the thermosetting resin is selected from at least one of epoxy resin, polyurethane-modified epoxy resin, acrylic-modified epoxy resin, polyamide resin, polyurethane resin and acrylic resin.

[0079] In one example, the thermosetting resin is epoxy resin.

[0080] In one example, the latent curing agent includes a latent amine curing agent and / or an imidazole curing agent. The latent curing agent can be a latent amine curing agent alone, an imidazole curing agent, or a combination of a latent amine curing agent and an imidazole curing agent.

[0081] Exemplarily, the latent amine curing agent is a dicyandiamide curing agent, which exemplarily includes MY-24, MY-25 and MY-HK-1.

[0082] Exemplarily, the imidazole curing agent includes PN-23J, PN-50, PN-23, PN-31 and PN-40.

[0083] In one example, the latent curing agent is a latent amine curing agent and an imidazole curing agent. The mass ratio of the latent amine curing agent and the imidazole curing agent is not limited and can be freely adjusted according to actual needs.

[0084] Exemplarily, the mass ratio of the thermosetting resin to the latent curing agent may be (4-6):1, for example, 4:1, 5:1, or 6:1.

[0085] The combination of latent amine curing agent and imidazole curing agent, and thermosetting resin, especially epoxy resin therein, to form a composite curing agent can make the copper electrode slurry cure faster and improve the bonding strength between the copper electrode slurry and the contact surface.

[0086] In one embodiment, the reducing dispersant is selected from at least one of polyvinyl pyrrolidone and its derivatives. The specific type of the derivative is not limited, for example, it can be a copolymer of polyvinyl pyrrolidone, or a reactant of polyvinyl pyrrolidone and other compounds, as long as the derivative can play a similar or better dispersing and reducing role as polyvinyl pyrrolidone.

[0087] In one example, the mass ratio of the metal composition to the dispersing reducing agent is (2-9):1, for example, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 8.74:1, 9:1.

[0088] In a preferred embodiment, the mass ratio of the metal composition to the dispersing reducing agent is (2.5-6):1.

[0089] The present invention selects polyvinyl pyrrolidone and its derivatives which have both dispersing and reducing effects as dispersing reducing agents, and limits the mass ratio of the metal composition and polyvinyl pyrrolidone and its derivatives, so that the copper electrode slurry has the advantages of good dispersibility and high reduction rate, improves the process efficiency of subsequent copper electrode preparation, and makes it easier to obtain copper electrodes with uniform thickness.

[0090] The type of solvent is not specifically limited, as long as it can dissolve the metal composition, disperse the reducing agent, and the composite curing agent, and does not react with the solute components. In one example, the solvent can be selected from C1-C6 low-carbon alcohols, or other types of organic solvents can be selected in the art.

[0091] In one example, the low-carbon alcohol includes at least one of ethylene glycol, polyethylene glycol, pentanol, propanol, butanol and isobutanol.

[0092] In one example, the mass ratio of the metal composition to the solvent is (0.3-2):1, for example, 0.3:1, 0.34:1, 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.86:1, or 2:1.

[0093] In a preferred embodiment, the mass ratio of the metal composition to the solvent is (1-1.6):1.

[0094] In one example, the mass ratio of the solvent to the dispersing reducing agent is (1.8-14):1, for example, it can be 1.8:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 13.6:1, 14:1.

[0095] In a preferred embodiment, the mass ratio of the solvent to the dispersing reducing agent is (2-5):1.

[0096] By limiting and optimizing the mass ratio of the metal composition and the solvent, as well as the mass ratio of the dispersing reducing agent and the solvent, the solid content of the copper electrode slurry can be controlled within an appropriate range, so that the copper electrode slurry contains more metal composition while having good dispersibility, which facilitates the coating of the copper electrode slurry and improves the thickness and uniformity of the prepared metal electrode.

[0097] In one example, the copper electrode slurry includes nano copper oxide, polyvinyl pyrrolidone, epoxy resin, latent amine curing agent, imidazole curing agent and ethylene glycol, wherein the proportion of each component is within the above-listed proportion range.

[0098] The present invention also provides a method for preparing a copper electrode slurry, which comprises the following steps:

[0099] (i) mixing the reducing dispersant and the solvent in the formulated amount in batches for multiple times to obtain a mixed solution under the combined action of heating, magnetic stirring and ultrasonic vibration;

[0100] (ii) adding the metal composition and the composite curing agent in the formulated amount to the mixed solution obtained in step (1) in batches for multiple times, and obtaining a copper electrode slurry under the combined action of heating, magnetic stirring and ultrasonic vibration.

[0101] The heating in steps (i) and (ii) can be performed in a water bath at 45-65° C. The number of batches is not limited and can be freely adjusted according to the different formulation contents.

[0102] The process conditions for heating, magnetic stirring and ultrasonic vibration in steps (i) and (ii) are not particularly limited and can be freely adjusted according to the amount and mixing state of the solution.

[0103] In one example, the metal electrode is a metal electrode in a solar cell, a secondary battery, a circuit board, a light emitting diode or a microelectronic device.

[0104] Preferably, the metal electrode is a metal electrode of a solar cell, for example, the metal electrode is a metal electrode (gate electrode) of a heterojunction cell.

[0105] The method for preparing a metal electrode of the present invention has a wider selection of substrates, and the substrate can be a semiconductor material and / or a conductor material. For example, the substrate can be at least one of single crystal silicon, polycrystalline silicon, ceramics, glass, flexible materials, metals and alloys. The method for preparing a metal electrode shown is particularly suitable for substrates that are not resistant to high temperatures, such as heterojunction battery substrates, and the processing temperature can be controlled below 200°C, reducing damage to the amorphous silicon layer.

[0106] The present invention also provides a method for preparing a solar cell grid line electrode, which uses the laser processing system described in the first aspect of the present invention and the copper electrode slurry described in the first aspect of the present invention to prepare a metal electrode, and particularly relates to a method for preparing a heterojunction solar cell grid line electrode.

[0107] In one example, referring to Figure 2 , Figure 3 and Figure 4 , the method for preparing a metal electrode for a solar cell comprises the following steps:

[0108] (1) placing a copper electrode slurry on the surface of a transparent conductive oxide film of a silicon substrate (e.g., a heterojunction battery substrate 17) to form a copper electrode slurry coating 19;

[0109] (2) Start the pulse laser and the continuous laser to obtain a laser composite beam 20, perform a first laser scan on the copper electrode slurry coating 19 on the surface of the transparent conductive film in step (1), and obtain a metal electrode 18.

[0110] In one example, in step (2), it is necessary to start the mobile working platform in advance to place the sample to be processed under the laser scanning system, and then start the pulse laser and the continuous laser to emit a laser beam. The laser beam emitted by the pulse laser passes through a half-wave plate, a first beam expander, a first reflector, a second reflector, a polarization reflector (e.g., a 45° polarization beam splitter), a diffractive optical element, a scanning galvanometer and a field mirror; the laser beam emitted by the continuous laser passes through the second beam expander and the third reflector and enters the polarization reflector (e.g., a 45° polarization beam splitter) to be combined with the pulse laser beam, and then coaxially passes through the diffractive optical element, the galvanometer (scanning galvanometer), and the f-θ field mirror to focus on the surface of the processed sample. Then, through the positioning sensor system and the CCD system (CCD camera), the coaxial laser beam after the combination is focused on the relative position of the surface of the sample to be processed, and finally the scanning galvanometer is used to control the combined laser beam to perform laser selective metal patterning on the surface of the sample to be processed according to the set processing path to prepare the copper electrode.

[0111] The inventors of the present invention have discovered that the use of a combination of pulsed laser and continuous laser can achieve remelting and solidification during selective metallization, thereby increasing adhesion while releasing the internal stress of the electrode, which can effectively reduce the porosity; it can also simplify the process flow, solve the problem of difficult position calibration in secondary processing, and improve processing efficiency.

[0112] In one example, in step (1), the thickness of the copper electrode slurry coating can be controlled by selecting coater parameters. Exemplarily, the thickness of the copper electrode slurry can be set to 1 μm-40 μm.

[0113] In one example, in step (1), the copper electrode slurry is disposed on the surface of the transparent conductive film by coating, and then dried to obtain a dry copper electrode slurry coating. The drying method is not specifically limited, as long as the purpose of drying can be achieved. For example, a drying oven can be used for drying, the drying temperature can be 50°C-70°C, and the drying time can be 20-40 minutes.

[0114] In one example, the pulse laser has no limitation on the pulse width and wavelength, and the pulse width may be femtosecond laser, picosecond laser or continuous laser; and the wavelength may be 300nm-1100nm.

[0115] In one example, the processing parameters of the pulse laser scanning are: laser pulse energy is 1nJ~500nJ, laser scanning speed is 1mm / s~500mm / s, defocus is +0mm~+2mm, laser pulse width is 100fs-20ps, frequency is 1KHz-70MHz, and laser wavelength is 300nm-1100nm.

[0116] In one example, the processing parameters of the continuous laser are: laser energy of 25nJ to 2000nJ, laser scanning speed of 1mm / s to 500mm / s, and defocus of +0mm to +2mm.

[0117] In one example, the method further includes step (3): turning off the pulse laser and continuing to start the continuous laser to perform the Nth laser scan on the copper electrode slurry of step (2), N≧2, and finally obtaining a metal electrode.

[0118] There is no limitation on the energy of the 2nd to Nth laser scans, and it can be less than, equal to or greater than the energy of the first laser scan.

[0119] In the present invention, copper circuits with different porosities, different aspect ratios and complex structures can be obtained by changing the laser parameters and the thickness of the copper electrode slurry coating, and copper circuits with different patterns can be obtained by arbitrarily changing the laser processing path, which has flexible controllability.

[0120] In one example, when the energy of the 2-Nth laser scan is greater than the energy of the first laser scan, the copper electrode can be remelted and solidified by increasing the laser energy, so that the copper electrode and the transparent conductive film are connected with high quality, thereby improving the adhesion of the electrode to the surface of the transparent conductive film.

[0121] In one example, when the energy of the 2-Nth laser scan is less than or equal to the energy of the first laser scan, the laser energy can be accumulated by increasing the value of N and performing multiple scans. The copper electrode can also be remelted and solidified to achieve high-quality connection between the copper electrode and the transparent conductive film, thereby improving the adhesion of the electrode to the surface of the transparent conductive film.

[0122] In one example, the laser energy of the 2nd to Nth laser scan is higher than the laser energy of the first laser scan. Preferably, the energy of the 2nd to Nth laser scan is higher, and the preset metal electrode can be obtained by reducing the number of scans, saving processing procedures.

[0123] The inventors of the present invention have found that since laser selective metal patterning is a photochemical reaction, the required temperature is relatively low, and it is difficult to achieve effective connection between the copper electrode and the transparent conductive film, and the adhesion is poor. Usually, sintering is required to improve the bonding strength between the copper electrode and the silicon substrate. The present invention can achieve remelting and solidification of the copper electrode by increasing the laser energy for a small number of scans, or multiple scans with a low accumulated laser energy, to achieve high-quality connection between the copper electrode and the transparent oxide conductive film, so as to improve the adhesion. At the same time, due to the high controllability of the laser, only the copper electrode can be processed, and no sintering is required, thereby avoiding damage to the amorphous silicon layer by the sintering furnace.

[0124] In one embodiment, the method for preparing a solar cell further comprises step (4): rinsing with deionized water to remove the remaining copper electrode slurry coating in the laser unprocessed area to obtain a heterojunction solar cell copper electrode. The cleaning solution is not limited to the deionized water listed above, and other cleaning solutions may also be applicable to the present invention.

[0125] In one example, the method for preparing a metal electrode for a solar cell further includes a step of pre-cleaning a transparent conductive oxide film, wherein the transparent conductive oxide film is cleaned with a water-based cleaning agent before the copper electrode slurry is provided.

[0126] In one example, the water-based cleaning agent includes a nonionic surfactant, an anionic surfactant, a defoaming agent, and a phosphate detergent builder.

[0127] In one example, based on the total weight of the water-based cleaning agent, the content of the nonionic surfactant is 16-21% by weight, the content of the anionic surfactant is 1-3% by weight, the content of the defoaming agent is 1-3% by weight, and the content of the phosphate detergent builder is 1.5-6% by weight. The remaining components are water, and the sum of the components is the total weight of the water-based cleaning agent, which is calculated as 100%.

[0128] In one example, the nonionic surfactant as a main active agent may be selected from at least one of polyoxyethylene glycol lauryl alcohol ether (AEO-9), fatty alcohol polyoxyethylene ether (JFC-3) and alkylphenol polyoxyethylene ether (TX-10).

[0129] In one example, the compounded anionic surfactant can be selected from at least one of sodium dodecyl diphenyl ether disulfonate (2A1), isooctyl alcohol polyoxyethylene ether phosphate and fatty acid hydroxyethane sulfonate.

[0130] In one example, the defoamer can be alcohols, amides, phosphates, polyethers, etc. For example, the defoamer is ethylenediamine PO-EO block copolymer (ED 3060), and other defoamers include tributyl phosphate, distearyl ethylenediamine, polyoxyethylene polyoxypropylene block copolymer, etc.

[0131] In one example, the phosphate detergent builder may be at least one of sodium tripolyphosphate, anhydrous sodium metaphosphate and sodium pyrophosphate.

[0132] In one example, based on the total weight of the water-based cleaning agent, the content of 2A1 is 1-3 weight %, the content of AEO-9 is 15-18 weight %, the content of JFC-3 is 1-3 weight %, the content of ED 3060 is 1-3 weight %, the content of sodium tripolyphosphate is 1-5 weight %, the content of anhydrous sodium metaphosphate is 0.5-1 weight %, and the remaining components are water.

[0133] In the present invention, the main components of the above-mentioned water-based cleaning agent are surfactants, detergent aids and buffer solutions, etc. The above-mentioned water-based cleaning agent is used to degrease and clean the silicon substrate of the heterojunction battery. During the cleaning process, the organic matter adsorbed on the surface of the silicon substrate can be removed by relying on the emulsification and saponification effects of the surfactant, thereby achieving the purpose of increasing the surface wettability and improving the surface tension, making the surface of the heterojunction battery easy to accept the coating, and improving the adhesion of the copper electrode slurry.

[0134] The method for preparing solar cell grid line electrodes provided by the present invention uses laser to selectively metal pattern the copper electrode slurry coating, which can directly obtain a copper line with a large aspect ratio and low resistivity, and will not cause damage to the laser unprocessed area, thereby improving the conversion efficiency of the solar cell. The method does not require multiple operations to increase the electrode thickness, nor does it require mask patterning and subsequent corrosion processes, and the process is simple. The method of multiple laser scanning can effectively increase the adhesion of the copper electrode, and can achieve the purpose of high efficiency and low cost.

[0135] The method for preparing metal electrodes provided by the present invention can be applied to a variety of fields, such as: solar cells, secondary batteries, circuit boards, light-emitting diodes or microelectronic devices, and can also be batteries or instruments and equipment in other technical fields. As long as they contain metal electrodes prepared by the method of the present invention, they are within the protection scope of the present invention.

[0136] A third aspect of the present invention provides a photovoltaic cell, comprising a metal electrode, wherein the metal electrode is prepared by the method described in the second aspect of the present invention.

[0137] Exemplarily, the photovoltaic cell is a solar cell. The solar cell is a silicon solar cell, specifically a monocrystalline silicon solar cell, a polycrystalline silicon thin film solar cell, and an amorphous silicon thin film solar cell. Preferably, it is a heterojunction solar cell, and it can also be other types of solar cells. As long as the metal electrode of the solar cell is prepared by the copper electrode slurry provided by the present invention, or prepared by the method for preparing a metal electrode of the present invention, it is within the protection scope of the present invention.

[0138] In one example, the basic structure of a heterojunction battery mainly includes an n-type single crystal silicon wafer (c-Si), an intrinsic amorphous silicon thin film layer (ia-Si:H), a doped amorphous silicon film layer amorphous silicon thin film (pa-Si:H), a transparent conductive film (ITO) and a metal gate electrode.

[0139] In one embodiment, a method for preparing a heterojunction solar cell comprises the following steps:

[0140] (I) performing texturing and cleaning on an n-type single crystal silicon wafer, i.e. forming a texturing surface ("pyramid structure") on the surface of the silicon wafer;

[0141] (II) deposition of an amorphous silicon film, including deposition of an intrinsic amorphous silicon film and a doped amorphous silicon film, firstly depositing an intrinsic amorphous silicon film (ia-Si:H) and a p-type amorphous silicon film (pa-Si:H) on the front side of an n-type single crystal silicon wafer (c-Si), and then depositing an intrinsic amorphous silicon film (ia-Si:H) and an n-type amorphous silicon film (na-Si:H) on the back side of the silicon wafer to form a back surface field;

[0142] (III) Depositing transparent oxide conductive films on both sides of the cell.

[0143] In one example, in step (I), the texturing and cleaning can cause the incident light to be reflected and refracted multiple times on the surface of the single crystal silicon wafer, thereby extending the optical path, increasing the photogenerated carriers, and avoiding the recombination of carriers at the junction interface caused by defects and impurities introduced by uncleanliness.

[0144] In one example, in step (II), the amorphous silicon film is deposited by plasma enhanced chemical vapor deposition and hot wire chemical vapor deposition. Superior surface passivation ability is an important condition for obtaining higher cell efficiency. By utilizing the excellent passivation effect of amorphous silicon, the minority carrier lifetime of silicon wafers can be greatly improved.

[0145] In one example, in step (III), the deposition method of the transparent conductive film includes various physical vapor deposition (PVD), chemical vapor deposition (CVD), jet pyrolysis and sol-gel. Since amorphous silicon has poor conductivity, adding a transparent conductive film between the electrode and the amorphous silicon layer during the manufacturing process of heterojunction solar cells can effectively increase the collection of carriers, and can also play an anti-reflection role, and is a good window layer material.

[0146] In one example, the intrinsic amorphous silicon film (ia-Si:H) has a thickness of 0.1-10 nm.

[0147] In one example, the thickness of the p-type amorphous silicon film (pa-Si:H) is 0.1-10 nm.

[0148] In one example, the thickness of the n-type amorphous silicon film (na-Si:H) is 0.1-10 nm.

[0149] In one example, the thickness of the transparent conductive film (ITO) is 1-400 nm.

[0150] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0151] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0152] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0153] Preparation Example 1

[0154] A copper electrode slurry, the formula of which is as follows:

[0155] Metal composition: nano copper oxide (CuO NP) with a particle size of 30-50 nm, 10 parts by weight;

[0156] Dispersing reducing agent: polyvinyl pyrrolidone, 3.26 parts by weight;

[0157] Composite curing agent: bisphenol A epoxy resin epoxy equivalent 182-192g / eq, viscosity 11000-14000, 0.5 parts by weight; PN-23J, 0.1 parts by weight;

[0158] Solvent: ethylene glycol, 6.76 parts by weight;

[0159] The copper electrode slurry is prepared by the following method:

[0160] (1) mixing the polyvinyl pyrrolidone and ethylene glycol in the formulated amounts in batches for multiple times (e.g., 4-5 times) and obtaining a mixed solution under the combined action of heating in a water bath at 45-65° C., magnetic stirring and ultrasonic vibration;

[0161] (2) Adding the formulated amount of nano copper oxide particles, epoxy resin and PN-23J to the mixed solution obtained in step (1) in batches for multiple times (for example, 4-5 times), and obtaining a copper electrode slurry under the combined action of heating in a water bath at 45-65° C., magnetic stirring and ultrasonic vibration.

[0162] Preparation Example 2

[0163] The preparation was carried out in accordance with Preparation Example 1, except that the copper electrode slurry had the following formula:

[0164] Metal composition: nano cuprous oxide (Cu2O NP), 10 parts by weight;

[0165] Dispersing reducing agent: polyvinyl pyrrolidone, 4 parts by weight;

[0166] Composite curing agent: polyurethane modified epoxy resin, 0.54 parts by weight; MY-25, 0.13 parts by weight;

[0167] Solvent: ethylene glycol, 10 parts by weight.

[0168] Preparation Example 3

[0169] The preparation was carried out in accordance with Preparation Example 1, except that the copper electrode slurry had the following formula:

[0170] Metal composition: CuO NP, 5 parts by weight, Cu2O NP, 5 parts by weight;

[0171] Dispersing reducing agent: polyvinyl pyrrolidone, 1.67 parts by weight;

[0172] Composite curing agent: acrylic modified epoxy resin, 0.43 parts by weight; PN-23J, 0.07 parts by weight;

[0173] Solvent: ethylene glycol, 6.25 parts by weight.

[0174] Preparation Example 4

[0175] This group of preparation examples is used to illustrate the effect of adjusting the components and proportions in the composite curing agent on the performance of the copper electrode slurry.

[0176] Preparation Example 4-1 was prepared by referring to Preparation Example 1, except that the composite curing agent was: epoxy resin, 0.83 parts by weight; PN-23J, 0.17 parts by weight;

[0177] Preparation Example 4-2 was prepared by referring to Preparation Example 1, except that the composite curing agent was: epoxy resin, 0.3 parts by weight; PN-23J, 0.3 parts by weight;

[0178] Preparation Example 4-3 was carried out with reference to Preparation Example 1, except that the composite curing agent was: epoxy resin, 0.5 parts by weight; PN-23J, 0.05 parts by weight; and MY-25, 0.05 parts by weight.

[0179] Preparation Example D1

[0180] The preparation was carried out in accordance with Preparation Example 1, except that 0.6 parts by weight of epoxy resin was used as a curing agent.

[0181] Preparation Example D2

[0182] The preparation was carried out in accordance with Preparation Example 1, except that 0.6 parts by weight of PN-23J was used as a curing agent.

[0183] Example 1

[0184] A solar cell is obtained by the following preparation method:

[0185] (1) preparing a heterojunction battery substrate and depositing a transparent conductive film (ITO) on both sides of the substrate;

[0186] Specifically, the preparation of the heterojunction battery substrate includes the following steps: after texturing and cleaning the n-type monocrystalline silicon wafer, an intrinsic amorphous silicon film (ia-Si:H) and a p-type amorphous silicon film (pa-Si:H) are sequentially deposited on the front of the n-type monocrystalline silicon wafer (c-Si), and then an intrinsic amorphous silicon film (ia-Si:H) and an n-type amorphous silicon film (na-Si:H) are sequentially deposited on the back of the silicon wafer to form a back surface field; a transparent oxide conductive film is deposited on both sides of the battery. The texturing and cleaning, the deposition method of the intrinsic amorphous silicon film, and the deposition method of the transparent conductive film are as described above and will not be repeated here. The specific process parameters are carried out in accordance with the conventional operating methods in the field.

[0187] The thickness of the intrinsic amorphous silicon film (ia-Si:H) is 5 nm;

[0188] The thickness of the p-type amorphous silicon film (pa-Si:H) is 5 nm;

[0189] The thickness of the n-type amorphous silicon film (na-Si:H) is 5 nm;

[0190] The thickness of the transparent conductive film (ITO) is 100 nm.

[0191] (2) Using a water-based cleaning agent to clean the ITO surface of the heterojunction battery to remove impurities and grease on the ITO surface; wherein the total weight of the water-based cleaning agent is used as a reference, AEO-9 16 weight%, JFC-3 2 weight%, 2A1 content is 2 weight%, ED 3060 2 weight%, sodium tripolyphosphate 4 weight%, anhydrous sodium metaphosphate 0.8 weight%, and the remaining components are water.

[0192] (3) Using a four-sided coater, the copper electrode slurry provided in Preparation Example 1 is applied to the surface of the heterojunction battery ITO cleaned in step (2), and dried in a drying oven at 50° C.-70° C. for 20-40 min to obtain a dry copper electrode slurry coating with a coating thickness of 7 μm-15 μm.

[0193] (4) A laser processing system is used to perform laser selective metal patterning on the dried copper electrode slurry coating according to a designed path; the structural schematic diagram of the laser processing system is shown in FIG. Figure 1 As shown; the specific operation process of the laser processing system is as follows:

[0194] S1: Start the mobile working platform and place the sample obtained in step (3) under the laser scanning system, then start the pulse laser and the continuous laser to emit a laser beam. The laser beam emitted by the pulse laser passes through a half-wave plate, a first beam expander, a first reflector, a second reflector, a 45° polarization beam splitter, a spatial light shaper, a scanning galvanometer and a field mirror; the laser beam emitted by the continuous laser passes through the second beam expander and the third reflector and enters the 45° polarization beam splitter to be combined with the pulse laser beam, and then coaxially passes through the laser spatial light shaper, the scanning galvanometer and the f-θ field mirror to be focused on the surface of the processed sample; wherein the Gaussian light is homogenized into a linear flat-top light by the spatial light shaper, and finally the flat-top light after shaping is used to selectively metal pattern the copper electrode slurry coating;

[0195] The processing parameters of pulse laser scanning are: laser pulse energy of 79 nJ, laser scanning speed of 6 mm / s, defocus of +0.6 mm, number of laser scans of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm.

[0196] The processing parameters of continuous laser scanning are: laser energy is 500 nJ, laser scanning speed is 6 mm / s, defocus amount is +0.6 mm, and the number of laser scanning is 1.

[0197] S2: Through the positioning sensor and CCD camera, the composite coaxial laser beam is focused on the relative position of the surface of the sample to be processed;

[0198] S3: Use a scanning galvanometer to control the composite laser beam to perform laser selective metal patterning on the surface of the sample to be processed according to the set processing path to prepare a copper electrode.

[0199] (5) Rinse with deionized water to remove the remaining copper electrode slurry coating in the unprocessed area to obtain a heterojunction solar cell copper electrode.

[0200] The three-dimensional morphology of the Cu gate line obtained in this embodiment is shown in the schematic diagram of the structure. Figure 5 As shown, a copper electrode with a uniform and fine surface and a line width of about 40 μm can be directly prepared by laser selective metal patterning. It should be noted that the copper electrode line width prepared by this laser processing system can be as small as 16 μm, but the improvement of resolution will lead to a decrease in resistivity, and the minimum width of the prepared copper electrode is related to the laser spot diameter. Changing the laser equipment can obtain a lower line width.

[0201] The surface of the copper electrode was observed using a field emission scanning electron microscope, and the elemental composition of the copper circuit was analyzed using EDS, such as Figure 6 As shown, it is found that the copper circuit structure obtained in this example is dense and can obtain a lower porosity; through X-ray energy spectrum analysis of element composition, the Cu:O of the copper electrode obtained in this example is increased from 1.8:1 before processing (copper electrode slurry) to 23.2:1, and the Cu / O content is greatly improved, reflecting that the Cu element is fully reduced at this time.

[0202] Example 2

[0203] The process is carried out with reference to Example 1, except that the processing parameters of the pulse laser scanning are: laser pulse energy of 100 nJ, laser scanning speed of 6 mm / s, defocusing amount of +0.4 mm, laser scanning number of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm. This embodiment can obtain a copper electrode with good surface morphology, low porosity, and dense structure.

[0204] Example 3

[0205] The process is carried out with reference to Example 1, except that the processing parameters of the pulse laser scanning are: laser pulse energy of 100 nJ, laser scanning speed of 5 mm / s, defocusing amount of +0.6 mm, laser scanning number of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm. This embodiment can obtain a copper electrode with good surface morphology, low porosity, and dense structure.

[0206] Example 4

[0207] The process was carried out with reference to Example 1, except that the processing parameters of the pulsed laser scanning were: laser pulse energy of 100 nJ, laser scanning speed of 8 mm / s, defocus of +0.6 mm, number of laser scans of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm. Due to the increase in scanning speed and the reduction reaction time, the copper electrode obtained in this example had poor continuity, but the overall morphology was complete.

[0208] Example 5

[0209] The process is carried out with reference to Example 1, except that the processing parameters of the pulse laser scanning are: laser pulse energy of 79 nJ, laser scanning speed of 6 mm / s, defocusing amount of +0.5 mm, laser scanning number of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm. This embodiment can obtain a copper electrode with good surface morphology, low porosity, and dense structure.

[0210] Example 6

[0211] The process was carried out in accordance with Example 1, except that the processing parameters of the pulsed laser scanning were: laser pulse energy of 79 nJ, laser scanning speed of 6 mm / s, defocus of +0.8 mm, number of laser scans of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm. Due to the increase in defocus, the laser energy density decreased, and although there were a few defects in the Cu circuit morphology obtained in this example, the overall morphology was complete.

[0212] Example 7

[0213] The process is carried out with reference to Example 1, except that the processing parameters of the continuous laser scanning are: laser energy of 500 nJ, laser scanning speed of 4 mm / s, defocusing amount of +0.8 mm, and laser scanning number of 1. This embodiment can obtain a copper electrode with good surface morphology, low porosity, and dense structure.

[0214] Examples 8-12

[0215] Examples 8-12 were carried out with reference to Example 1, except that in step (4) of Examples 8-12, the copper electrode slurries prepared by Preparation Example 2, Preparation Example 3, Preparation Example 4-1, Preparation Example 4-2 and Preparation Example 4-3 were used respectively.

[0216] Embodiment 13

[0217] The method is carried out in accordance with Example 1, except that the Gaussian light is homogenized into a rectangular flat-top light by a spatial light shaper, and finally the shaped flat-top light is used to perform selective metal patterning on the copper electrode slurry coating.

[0218] Embodiment 14

[0219] The process is carried out in accordance with Example 1, except that after the laser scanning in step (4) is completed, 50 laser scans are further performed, and the processing parameters of the 2nd to 50th laser scans are: laser pulse energy of 35nJ, laser scanning speed of 6mm / s, defocus of +0.6mm, laser pulse width of 9ps, repetition frequency of 2MHz, and laser wavelength of 532nm.

[0220] Comparative Example 1

[0221] This comparative example is the same as Example 1, except that the laser parameters used in the pulse laser processing are: laser pulse energy of 35nJ, laser scanning speed of 6mm / s, defocus of +0.6mm, laser scanning number of 1, laser pulse width of 9ps, repetition frequency of 2MHz, and laser wavelength of 532nm. It can be found that the lower energy is not enough to completely reduce CuO to Cu, and the resulting copper circuit morphology is not good.

[0222] Comparative Example 2

[0223] This comparative example is the same as Example 1, except that the laser parameters used in the pulse laser processing are: laser pulse energy of 100nJ, laser scanning speed of 2mm / s, defocus of +0.6mm, laser scanning number of 1, laser pulse width of 9ps, repetition frequency of 2MHz, and laser wavelength of 532nm. The copper circuit obtained in this example is severely oxidized due to the slow scanning speed.

[0224] Comparative Example 3

[0225] This comparative example is the same as Example 1, except that the laser parameters used in the pulse laser processing are: laser pulse energy of 79nJ, laser scanning speed of 6mm / s, defocus of +0.2mm, laser scanning number of 1, laser pulse width of 9ps, repetition frequency of 2MHz, and laser wavelength of 532nm. Due to the small spot diameter and excessive laser energy density, the CuO nano-coating was ablated and a good copper circuit could not be restored.

[0226] Comparative Example 4

[0227] This comparative example is the same as Example 1, except that the continuous laser scanning parameters are: laser energy of 800nJ, laser scanning speed of 6mm / s, defocusing amount of +0.6mm, and laser scanning number of 1. The metallographic image of the prepared Cu circuit was tested in the same way as in Example 1, and it was found that due to excessive energy, the copper electrode was ablated and gasified, and a good copper circuit could not be obtained.

[0228] Comparative Examples 5-6

[0229] The process was carried out with reference to Example 1, except that in step (3) of Comparative Examples 5 and 6, the copper electrode slurries prepared in Preparation Example D1 and Preparation Example D2 were used respectively.

[0230] Test Case

[0231] (1) For the solar cells obtained in the above Examples 1-14 and Comparative Examples 1-6, the resistivity of the metal electrodes was measured using a four-probe method. The results are recorded in Table 1.

[0232] (2) For the above-mentioned embodiments 1-14 and comparative examples 1-6, solar cells were obtained, and the binding strength of the metal electrodes was tested by the Hundred Grids method, wherein the test results were divided into six levels: 0B, 1B, 2B, 3B, 4B, and 5B, 0B-5B representing a greater binding strength, that is, 5B has the strongest binding strength. The results are recorded in Table 1.

[0233] Table 1

[0234] Group Resistivity (μΩ.cm) Binding force Example 1 41.2 3B Example 2 48.3 3B Example 3 60.5 3B Example 4 408.6 3B Example 5 45.2 3B Example 6 489.2 2B Example 7 48.9 3B Example 8 73.5 3B Example 9 79.6 2B Example 10 198.7 2B Embodiment 11 84.2 1B Example 12 71.5 2B Embodiment 13 40.1 3B Embodiment 14 50.9 3B Comparative Example 1 130.2 2B Comparative Example 2 299.4 2B Comparative Example 3 346.5 2B Comparative Example 4 799.6 2B Comparative Example 5 74.8 1B Comparative Example 6 71.9 1B

[0235] It can be seen from the experimental data in Table 1 that the method of preparing heterojunction solar cell copper electrodes by laser selective metal patterning, combined with the copper electrode slurry provided by the present invention, can obtain gate line electrodes with low resistivity and high bonding strength, and the laser multiple scanning method can effectively increase the bonding strength of the copper electrode.

[0236] In addition, it can be seen from the above experimental data that changing the total content of the composite curing agent will change the resistivity and adhesion. A high content of the composite curing agent will lead to an increase in the resistivity, and a low content of the composite curing agent will affect the adhesion. The internal ratio of the composite curing agent affects the curing effect, that is, the bonding force, and has little effect on the resistivity. The structure mainly affects the bonding force and has little effect on the resistivity. Combined with multiple laser processing, the resistivity can be reduced and the adhesion can be improved.

[0237] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A laser processing system, characterized in that: Used to prepare metal electrodes for solar cells, the laser processing system comprises: a mobile working platform, a first optical path system, a second optical path system and a composite optical path system; The mobile working platform is used to carry the substrate of the metal electrode to be prepared; The first optical path system includes a pulse laser and a first optical path adjustment system, the pulse laser is used to emit a pulse laser, and the pulse laser passes through the first optical path adjustment system to form a first light beam; The second optical path system comprises a continuous laser and a second optical path adjustment system, wherein the continuous laser is used to emit a continuous laser, and the continuous laser passes through the second optical path adjustment system to form a second light beam; The composite optical path system receives the first light beam and the second light beam to form a composite light beam, and the composite light beam acts on the substrate of the metal electrode to be prepared.

2. The laser processing system according to claim 1, wherein: The first optical path adjustment system comprises a first optical element, a first beam expander and a first reflector group which are arranged in sequence, wherein the first optical element group is close to the pulse laser, the first reflector group is close to the composite optical path system, and the first optical element is used to adjust the polarization of the pulse laser; Preferably, the second optical path adjustment system comprises a second beam expander and a third reflector which are sequentially arranged, wherein the second beam expander is close to the continuous laser, the third reflector is close to the composite optical path system, and the third reflector is arranged at a first preset angle with the second beam expander; Preferably, the composite optical path system comprises a polarizing reflector, a diffractive optical element, a galvanometer mirror and a field lens which are arranged in sequence.

3. The laser processing system according to claim 2, wherein: The first reflector group includes a first reflector and a second reflector, the first reflector is close to the first beam expander and is arranged at a second preset angle with the first beam expander, and the second reflector is arranged parallel to the first reflector and is close to the composite optical path system; Preferably, the polarizing reflector and the second reflector are arranged at a third preset angle to completely transmit the first light beam; Preferably, the polarizing reflector is arranged in parallel with the third reflector to partially transmit the second light beam.

4. The laser processing system according to claim 3, wherein: Also included is a monitoring device, which is coaxially arranged with the galvanometer and is used to monitor the processing process of the composite light beam; Preferably, the laser processing system further comprises a positioning sensor, which is arranged on the galvanometer and is used to determine the processing position of the composite light beam.

5. A method for preparing a metal electrode, characterized in that: The metal electrode is prepared by using the laser processing system and copper electrode slurry described in any one of claims 1 to 4.

6. The method according to claim 5, wherein: The copper electrode slurry comprises a metal composition, a dispersing reducing agent, a composite curing agent and optionally a solvent; the metal composition comprises at least copper powder, and optionally gold powder and / or silver powder; the composite curing agent comprises a thermosetting resin and a latent curing agent; And / or, the metal electrode is a metal electrode in a solar cell, a secondary battery, a circuit board, a light emitting diode or a microelectronic device; preferably, it is a metal electrode of a solar cell.

7. The method according to claim 5 or 6, wherein: The thermosetting resin is selected from at least one of epoxy resin, polyurethane-modified epoxy resin, acrylic-modified epoxy resin, polyamide resin, polyurethane resin and acrylic resin; And / or, the latent curing agent includes a latent amine curing agent and / or an imidazole curing agent; And / or, the reducing dispersant is selected from at least one of polyvinyl pyrrolidone and its derivatives; And / or, the solvent is selected from C1-C6 low-carbon alcohols; And / or, the metal composition includes nano copper oxide and / or nano cuprous oxide.

8. The method according to claim 5 or 6, wherein: The mass ratio of the metal composition to the composite curing agent is (7-30):1; And / or, the mass ratio of the thermosetting resin to the latent curing agent is (4-6):1; And / or, the mass ratio of the metal composition to the composite curing agent is (15-20): 1 And / or, the mass ratio of the metal composition to the dispersing reducing agent is (2-9):1, preferably (2.5-6):

1.

9. The method according to claim 6, wherein: The method for preparing a metal electrode for a solar cell comprises the following steps: (1) placing a copper electrode slurry on the surface of a transparent conductive oxide film on a silicon substrate; (2) starting the pulse laser and the continuous laser to obtain a composite light beam, and performing a first laser scan on the copper electrode slurry coating on the surface of the transparent conductive film in step (1); Preferably, the method further comprises step (3): performing an Nth laser scan on the copper electrode slurry of step (2), where N≧2; Preferably, the laser energy of the Nth laser scan is higher than the laser energy of the first laser scan.

10. A photovoltaic cell comprising a metal electrode, characterized in that: The metal electrode is prepared by the method according to any one of claims 5 to 9.

Citation Information

Patent Citations

  • Processing device and method for preparing silver paste electrode by laser-induced forward transferring printing and sintering

    CN109926583A

  • Electrode slurry for heterojunction solar cell and preparation method thereof

    CN111048233A

  • Method for preparing flexible copper circuit by laser-induced reduction sintering of copper oxide ink

    CN111970842A

  • Mask-free preparation method of copper electrode of heterojunction solar cell

    CN113066897A

Cited By

  • Photovoltaic cell, preparation method thereof and photovoltaic module

    CN120187148A